Implementasi Susunan Tumpukan Dus untuk Menghilangkan Penggunaan Tali Pengikat - Dendy Setiady; Luis Anderson (Universitas Bunda Mulia, 2017)
Today, instant noodles is a food substitute for the most frequently consumed by the public, because of the high activity and mobility of people, so that indirectly resulted in increased consumption of instant noodles that are considered the most feasible and practical in its presentation. Problem arise which serve as the topic by researchers are: How does the composition of boxes to stack remained robust without straps? And how do researcher cope with that palette which wont damaged when operated using a forklift. Data used in this study, through direct interviews, observation, sampling, and direct experiment. In determining the sampling researchers using simple random sampling method from the number of samples to be taken as many as 323 pallets in warehouses PT. XYZ branch Ancol. Researchers can conclude that the way the current composition of the pile is less sturdy boxes that require the use of straps as a drag on the top of the box so as not to swell and fall. Based on the results of the analysis and experiments, researchers found a more ideal arrangement sturdy box even without the rope. Perform modifications on forklift forks, as based on observation and analysis, researchers with a fork width of only 76 Cm forklifts, not balanced with measures that are currently used pallets (150 x 130 cm), so that the pallet tends to curl at the time appointed. Modifications can be done by adding the width of the forklift forks.Keywords: Material Handling, Warehouse, Boxes Arrangement